Self‐Orienting Hydrogel Micro‐Buckets as Novel Cell Carriers. Issue 2 (27th November 2018) - Liu, Qian; Zhao, Meng; Mytnyk, Serhii; Klemm, Benjamin; Zhang, Kai; Wang, Yiming; Yan, Dadong; Mendes, Eduardo; van Esch, Jan H.
Abstract: Hydrogel microparticles are important in materials engineering, but their applications remain limited owing to the difficulties associated with their manipulation. Herein, we report the self‐orientation of crescent‐shaped hydrogel microparticles and elucidate its mechanism. Additionally, the microparticles were used, for the first time, as micro‐buckets to carry living cells. In aqueous solution, the microparticles spontaneously rotated to a preferred orientation with the cavity facing up. We developed a geometric model that explains the self‐orienting behavior of crescent‐shaped particles by minimizing the potential energy of this specific morphology. Finally, we selectively modified the particles' cavities with RGD peptide and exploited their preferred orientation to load them with living cells. Cells could adhere, proliferate, and be transported and released in vitro. These micro‐buckets hold a great potential for applications in smart materials, cell therapy, and biological engineering. Abstract : There 's a cell in my bucket : The self‐orientation of crescent‐shaped hydrogel microparticles was reported and its mechanism elucidated. These microparticles were used as cell carriers for cell loading, transport, proliferation, and release after functionalization with cell‐adhesive peptides. This provides a new strategy for manipulation of microparticles with potential applications in biomaterials, tissue architecture, and cell delivery.